PENGARUH ENVIRONMENTAL PERFORMANCE, CORPORATE GOVERNANCE, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Rima Sekar Ayu Cahyani; Sekar Mayangsari (Jurnal Ekonomi Trisakti, 2022)
This study aims to examine the effect of environmental performance, corporate governance, and corporate social responsibility on the financial performance of food & beverage companies on the Indonesia Stock Exchange in 2018 – 2020. The independent variables in this study are PROPER, Audit Committee, Proportion of Independent Commissioners, Ownership Managerial, Institutional Ownership, and CSR. While the dependent variable in this study is the company's financial performance. The sampling technique was carried out using the purposive sampling method, namely the technique of determining the sample with certain considerations. Data analysis techniques include (1) Descriptive Statistics (2) Classical Assumption Test includes Normality, Multicollinearity, Heteroscedasticity, and Autocorrelation (3) Multiple Linear Regression Testing (4) F Statistical Test (5) Hypothesis Testing (6) R2 Test. The sample used in this study is food & beverage companies listed on the Indonesia Stock Exchange in 2018 - 2020, with a total of 31 companies per year and there are 93 research samples that meet the criteria. The results of this study conclude that the PROPER variable affects the company's financial performance, the audit committee variable, the proportion of independent commissioners, managerial ownership, institutional ownership affects the company's financial performance, and CSR has an effect on the company's financial performance. Tujuan penelitian guna menguji pengaruh environmental performance, corporate governance, dan corporate social responsibility terhadap kinerja keuangan perusahaan food & beverage di Bursa Efek Indonesia pada tahun 2018 – 2020. PROPER, Komite Audit, Kepemilikan Manajerial, Proporsi Dewan Komisaris Independen, Kepemilikan Institusional, dan CSR dijadikan variabel bebas penelitian ini. Sementara kinerja keuangan perusahaan dijadikan variabel terikat penelitian ini. Metode purposive sampling dijadikan sebagai teknik sampling yakni dengan mengacu suatu pertimbangan khusus. Data dianalisis melalui teknik (1) Statistik Deskriptif (2) Uji Asumsi Klasik (3) Analisis Regresi Linear Berganda (4) Uji Hipotesis (5) Uji Statistik F (6) Uji R2. Sejumlah 31 perusahaan food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2018 – 2020 dijadikan sampel penelitian ini serta serta sampel yang sesuai kriteria didapatkan sejumlah 93. Penelitian menghasilkan yaitu variabel PROPER berpengaruh terhadap kinerja keuangan perusahaan, variabel komite audit, proporsi dewan komisaris independen, kepemilikan manajerial, kepemilikan institusional berpengaruh terhadap kinerja keuangan perusahaan, dan CSR berpengaruh terhadap kinerja keuangan perusahaan.